Stratigraphy and mineralogy of Candor Mensa, West Candor Chasma, Mars: Insights into the geologic history of Valles Marineris. Issue 2 (7th February 2014) - Fueten, F.; Flahaut, J.; Stesky, R.; Hauber, E.; Rossi, A. P.
Abstract Candor Mensa, an interior layered deposit (ILD) in Valles Marineris, Mars, consists of two stratigraphically distinct units, the lower of which comprises the bulk of the mensa. This lower unit is approximately 5 km thick and composed of parallel layers, 4 to 14 m in thickness and associated with monohydrated sulfates. The lower unit is disconformably overlain by an upper unit composed of thinner (< 3 m) layers with diagnostic polyhydrated sulfate signatures. The original extent of proto‐Candor Mensa and its lower unit included neighboring Baetis Mensa. We suggest that the source material for both units is airborne dust or ash but that the depositional environment for the units differs. First, the lower unit was deposited during the subsidence of an enclosed water‐filled basin. This basin/lake could have been frozen periodically, with freeze‐thaw episodes possibly linked to Martian obliquity cycles. Erosion, including the potential action of glaciers, was able to remove large volumes of material out of the basin during the tectonism that produced the current geometry of Valles Marineris. Deposition of the upper unit postdates this event and took place in the absence of standing water at high elevation. Groundwater or snowmelt may have provided the water required for sulfate formation and deposit induration. We conclude that the major break in sedimentation recorded by this ILD deposit coincides with linking of ancestral basins into the current geometry of Valles Marineris chasmata and that it was possible to form hydrated minerals after this event.